Use of information and communication technologies by Family Health Extended Centers - Carine Vendruscolo; Daniela Savi Geremia; Edlamar Kátia Adamy; Lara Vandresen; Lucimare Ferraz (Universidade Federal de Santa Maria, 2020)
Objective: To analyze the use of information and communication technologies by Family Health Extended Centers and to reflect on their potential for care. Method: study of mixed methods, with a quantitative sample of 359 professionals from the nuclei, in 149 municipalities, with survey application, and qualitative step comprising focus groups with five teams, 43 from the nuclei. Data was collected between May and November 2017 and treated according to descriptive statistical approach and thematic analysis. Results: Among technologies, electronic medical records and dialogue between professionals of the Family Health teams and the nuclei are highlighted. Dialogue with community agents is frequent, but there is little participation of health leaders and counselors. Conclusion: Despite the advances, the use of technologies still does not reach its full potential for care, and one must stimulate dialogue among teams, the use of territory map and social participation.